Xi Jinping's visit to South Korea : Finlandisation or Crimeanisation? - Yoon, Sukjoon (2014)
The Chinese President's recent state visit to Seoul may presage either 'Finlandisation' in which South Korea shrewdly retains some degree of self-reliance by balancing between the great powers; or 'Crimeanisation' with Seoul's interests increasingly subsumed within China's larger geopolitical influence.